The World Bank Legal Review, Volume 6. Improving Delivery in Development : The Role of Voice, Social Contract, and Accountability - Wouters, Jan; Ninio, Alberto; Doherty, Teresa; Cissé, Hassane (Washington, DC: World Bank, 2015)
In recent years, better delivery in development has been at the center of development discourse. There is now wide agreement that today’s development challenges demand effective solutions that fully integrate the aspirations, voices, needs, and support of citizens. But how can the international community translate that realization into practical accomplishment? Volume 6 of The World Bank Legal Review examines delivery challenges through the lens of three concepts that are critical to better development outcomes: voice, social contract, and accountability. The volume turns a spotlight on the nature of this interlocking trio, revealing that their consistent integration into both the design and the implementation of development efforts is indispensable if successful outcomes are to result. Written by seasoned practitioners and eminent scholars from across the globe, the volume’s 24 chapters illuminate the importance of a multidisciplinary approach to development. Development practitioners devoted to rule of law and justice must work with experts from various disciplines to create a synergistic dynamic that can optimize the integration of voice, social contract, and accountability into development efforts.